Human Placenta Blood Flow During Early Gestation With Pseudocontinuous Arterial Spin Labeling MRI. Issue 4 (4th November 2019) - Liu, Dapeng; Shao, Xingfeng; Danyalov, Alibek; Chanlaw, Teresa; Masamed, Rinat; Wang, Danny J.J.; Janzen, Carla; Devaskar, Sherin U.; Sung, Kyunghyun
Abstract : Background: Noninvasive measurement of placental blood flow is the major technical challenge for predicting ischemic placenta (IPD). Pseudocontinuous arterial spin labeling (pCASL) MRI was recently shown to be promising, but the potential value in predicting the subsequence development of IPD is not known. Purpose: To derive global and regional placental blood flow parameters from longitudinal measurements of pCASL MRI and to assess the associations between perfusion‐related parameters and IPD. Study Type: Prospective. Population: Eighty‐four women completed two pCASL MRI scans (first; 14–18 weeks and second; 19–24 weeks) from prospectively recruited 118 subjects. A total of 69 subjects were included for the analysis, of which 15 subjects developed IPD. Field Strength/Sequence: 3T/T2 ‐weighted half‐Fourier single‐shot turbo spin‐echo (HASTE) and pCASL. Assessment: Four perfusion‐related parameters in the placenta were derived: placenta volume, placental blood flow (PBF), high PBF (hPBF), and relative hPBF. The longitudinal changes of the parameters and their association with IPD were tested after being normalizing to the 16th and 20th weeks of gestation. Statistical Tests: Comparisons between two gestational ages within subjects were performed using the paired Wilcoxon tests, and comparisons between normal and IPD groups were performed using the unpaired Wilcoxon tests. Results: The difference between the first and second MRI scans was statistically significant for volume (156.6 cm 3 vs. 269.7 cm 3, P  < 0.001) and PBF (104.9 ml/100g/min vs. 111.3 ml/100g/min, P = 0.02) for normal subjects, indicating an increase in pregnancy with advancing gestation. Of the parameters tested, the difference between the normal and IPD subjects was most pronounced in hPBF (278.1 ml/100g/min vs. 180.7 ml/100g/min, P  < 0.001) and relative hPBF (259.1% vs. 183.2%, P  < 0.001) at 16 weeks. Data Conclusion: The high perfusion‐related image parameters for IPD were significantly decreased from normal pregnancy at 14–18 weeks of gestation. Level of Evidence: 2 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2020;51:1247–1257.